A Renal Inflammatory Myofibroblastic Tumor Similar to Cystic Renal Cell Carcinoma. Issue 28 (July 2015) - Liang, Wenjie; Gong., Yanjun
<x xml:space="preserve">Abstract</x> Abstract We describe and analyze the clinical course and imaging findings of a case of a renal inflammatory myofibroblastic tumor (IMT) that is similar to cystic renal cell carcinoma. "Solitary cysts" on the left kidney were found during a health examination of a 60-year-old female. The patient also had hypertension. She had undergone surgeries twice for limb trauma fracture and had no definite record of hepatitis. There was no tenderness with percussion of the kidney area or edema in the lower extremity. The renal function results, including serum creatinine, blood urea nitrogen, and blood urea, were within the normal range. No gross hematuria or microscopic hematuria was found. An 8.7 cm × 9.2 cm mixed echogenic mass at the upper pole of the left kidney was observed with ultrasound, the majority of which was an anechoic mass that was slightly protruding from the renal capsule and had well-circumscribed borders. After a bolus injection of an ultrasound contrast agent, the mass had rapid enhancement with fast fading. An approximately 9.4 cm × 10.1 cm round-like cyst lesion at the upper pole of the left kidney was revealed by computed tomography (CT) examination of the abdomen; it had edge finishing with well-circumscribed borders. The upper inner wall of the lesion was thick with crescentic soft tissue. The solid content had gradual enhancement on enhanced CT scans. A kidney tumor was considered based on the CT findings. Based on the preoperative examination, the left renal cystic masses were resected. Intraoperative frozen sections were used to further clarify the nature of the lesion, and no significant malignant cells were observed; therefore, the kidney was not removed. The pathological diagnosis was renal IMT. After surgery, the patient recovered and did not have recurrence or metastasis over the course of long-term follow-up. CT images of our patient with renal cystic disease are categorized as Fuhrman grade IV and typically indicate the presence of malignant lesions. However, gradual enhancement of the solid content in our case is different from typical cystic renal cell carcinoma. The nature of the lesion was further identified using intraoperative frozen sections, which helped avoid unnecessary nephrectomy.